SYNTHESIS OF PEROFSKITE-LIKE Co-CONTAINING CATALYST - G.D. Jetpisbayeva; B.K. Massalimova; A.B. Daulet (Academic Scientific Journal of Chemistry, 2020)
There are several approaches to the preparation of catalysts with a developed surface based on oxides with a perovskite structure. Perovskites, due to the possibility of easy variation of chemical composition, make it possible to choose the optimal composition of the catalyst and surface area, and as a result it is possible to influence effectively the selectivity. Perovskite-like LaMeO3 oxides are one of the most promising catalysts for many oxidation processes due to their high activity in oxidative reactions and the stability in aggressive environment. Pekini method (polymer complexes method) and its simplified variant - citrate method are the most widely used for the synthesis of perovskite-like oxides. This article reports about the synthesis of perovskite-like complex oxide LaCoO3 obtained in two ways: hydrothermal, using ethylene glycol, and the citrate method using the template – mesoporous silica KIT-6. The structure of the samples obtained was determined by the XRD method. As a result, it was found that the catalysts have a perovskite structure